Se ha denunciado esta presentación.
Utilizamos tu perfil de LinkedIn y tus datos de actividad para personalizar los anuncios y mostrarte publicidad más relevante. Puedes cambiar tus preferencias de publicidad en cualquier momento.

My MSc. Project

454 visualizaciones

Publicado el

Publicado en: Educación, Tecnología
  • Sé el primero en comentar

  • Sé el primero en recomendar esto

My MSc. Project

  1. 1. Simulation and Experiment of the Interaction of Pulsed Light with Multilevel Systems Abhijit Mondal Y6010 Department of Chemistry Indian Institute of Technology, Kanpur
  2. 2. ∂c1/∂t = i(E0 μ12/2ħ) (ei(ω−ω0)t + e−i(ω+ω0 )t ) c2 (t) ∂c2/∂t = i(E0 μ12/2ħ) (e-i(ω−ω0)t + ei(ω+ω0 )t ) c1 (t) where E0 is the amplitude of the light wave, light wave of angular frequency ω and ω0 = (E2 − E1 )/ħ. Rabi frequency defined by: ΩR = |μ12 E0 /ħ |. We apply the rotating wave approximation to neglect the terms that oscillate at ±(ω + ω0 ),Second, we only consider the case of exact resonance with δω = 0.
  3. 3. NOT GateHadamardGate
  4. 4. int main(int argc,char *argv[]){ FILE *fp1,*fp2,*fp3,*fp4; fp1=fopen("1.txt","r"); fp2=fopen("gr 5.txt","r"); fp3=fopen("quotient.txt","w"); fp4=fopen("remainder.txt","w"); char *buffer1=new char[20]; char *buffer2=new char[20]; double *f=new double[2000]; double *g=new double[2000]; int i=0; while(!feof(fp1)) {fseek(fp1,7,SEEK_CUR); fgets(buffer2,8,fp1); double y=atof(buffer2); f[i]=y;i+ +; } i=0; while(!feof(fp2)) {fseek(fp2,7,SEEK_CUR); fgets(buffer2,8,fp2); double y=atof(buffer2); g[i]=y;i+ +; } int deg=i; for(i=0;i<deg;i++) { int j=1;double sum=0.0; while(j<=i) {sum+=f[j]*q[i-j]; j++; } q[i]=(g[i]-sum)/f[0]; fprintf(fp3,"%fn",q[i]); }}
  5. 5. Let us suppose that the original response signal be denoted as g(x), the h(x) is the convolution of f(x) and g(x). Then c0= a0 b0= c0 / a0 c1= a1b0 + a0b1 b1= (c1- a1b0) / a0 c 2= a2b 0 + a 1b 1 + a 0b 2 b2= (c2- a1b1- a2b0) / a0 . . cn-1= ∑i=0n-1 ai bn-1-i bn-1= (cn-1 - ∑i=1n-1 ai bn-1-i) / a0Hence we use a dynamic programming approach to solve for bi for each i as: bi = (ci - ∑j=1i aj bi-j) / a0
  6. 6. Thank You for noticing me !!!

×